Fit-for-work or fit-for-unemployment? Does the reassessment of disability benefit claimants using a tougher work capability assessment help people into work?. Issue 5 (8th December 2015) - Barr, B; Taylor-Robinson, D; Stuckler, D; Loopstra, R; Reeves, A; Wickham, S; Whitehead, M
Abstract : Background: Many governments have introduced tougher eligibility assessments for out-of-work disability benefits, to reduce rising benefit caseloads. The UK government initiated a programme in 2010 to reassess all existing disability benefit claimants using a new functional checklist. We investigated whether this policy led to more people out-of-work with long-standing health problems entering employment. Method: We use longitudinal data from the Labour Force Survey linked to data indicating the proportion of the population experiencing a reassessment in each of 149 upper tier local authorities in England between 2010 and 2013. Regression models were used to investigate whether the proportion of the population undergoing reassessment in each area was independently associated with the chances that people out-of-work with a long-standing health problem entered employment and transitions between inactivity and unemployment. We analysed whether any effects differed between people whose main health problem was mental rather than physical. Results: There was no significant association between the reassessment process and the chances that people out-of-work with a long-standing illness entered employment. The process was significantly associated with an increase in the chances that people with mental illnesses moved from inactivity into unemployment (HR=1.22, 95% CI 1.03 to 1.45). Conclusions: The reassessment policy appears to have shifted people with mental health problems from inactivity into unemployment, but there was no evidence that it had increased their chances of employment. There is an urgent need for services that can support the increasing number of people with mental health problems on unemployment benefits.